Smaller Body Size, Early Postnatal Lethality, and Cortical Extracellular Matrix-Related Gene Expression Changes of Cyfip2-Null Embryonic Mice - Zhang, Yinhua; Kang, Hyojin; Lee, Yeunkum; Kim, Yoonhee; Lee, Bokyoung; Kim, Jin Yong; Jin, Chunmei; Kim, Shinhyun; Kim, Hyun; Han, Kihoon (Frontiers in Molecular Neuroscience, 2019)
Cytoplasmic FMR1-interacting protein 2 (CYFIP2) is a key component of the WAVE regulatory complex (WRC) which regulates actin polymerization and branching in diverse cellular compartments. Recent whole exome sequencing studies identified de novo hotspot variants in CYFIP2 from patients with early-onset epileptic encephalopathy and microcephaly, suggesting that CYFIP2 may have some functions in embryonic brain development. Although perinatal lethality of Cyfip2-null (Cyfip2-/-) mice was reported, the exact developmental time point and cause of lethality, and whether Cyfip2-/- embryonic mice have brain abnormalities remain unknown. We found that endogenous Cyfip2 is mainly expressed in the brain, spinal cord, and thymus of mice at late embryonic stages. Cyfip2-/- embryos did not show lethality at embryonic day 18.5 (E18.5), but their body size was smaller than that of wild-type (WT) or Cyfip2+/- littermates. Meanwhile, at postnatal day 0, all identified Cyfip2-/- mice were found dead, suggesting early postnatal lethality of the mice. Nevertheless, the brain size and cortical cytoarchitecture were comparable among WT, Cyfip2+/-, and Cyfip2-/- mice at E18.5. Using RNA-sequencing analyses, we identified 98 and 72 differentially expressed genes (DEGs) from the E18.5 cortex of Cyfip2+/- and Cyfip2-/- mice, respectively. Further bioinformatic analyses suggested that extracellular matrix (ECM)-related gene expression changes in Cyfip2-/- embryonic cortex. Together, our results suggest that CYFIP2 is critical for embryonic body growth and for early postnatal survival, and that loss of its expression leads to ECM-related gene expression changes in the embryonic cortex without severe gross morphological defects.